2022
DOI: 10.1063/5.0100424
|View full text |Cite
|
Sign up to set email alerts
|

Cascade neural approximating for few-shot super-resolution photoacoustic angiography

Abstract: High-resolution photoacoustic angiography images are reconstructed from undersampled images with the help of a super-resolution deep neural network, enhancing the ability of the photoacoustic angiography systems to image dynamic processes in living tissues. However, image degradations are difficult to estimate due to a lack of knowledge of the point spread function and noise sources, resulting in poor generalization capability of the trained super-resolution model. In this work, a high-order residual cascade n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Evaluations showed that it achieved substantially higher vessel contrast at depths over 2 cm in vivo. Other super-resolution methods include works by Ma et al 107 and He et al 108 High fidelity deconvolution methods, such as using RRDBNet, 109 also leverage deep learning for resolution improvement. RRDBNet is a deep residual network tailored for image deconvolution.…”
Section: Non-contact Light-based Acoustic Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluations showed that it achieved substantially higher vessel contrast at depths over 2 cm in vivo. Other super-resolution methods include works by Ma et al 107 and He et al 108 High fidelity deconvolution methods, such as using RRDBNet, 109 also leverage deep learning for resolution improvement. RRDBNet is a deep residual network tailored for image deconvolution.…”
Section: Non-contact Light-based Acoustic Sensormentioning
confidence: 99%
“…Evaluations showed that it achieved substantially higher vessel contrast at depths over 2 cm in vivo . Other super-resolution methods include works by Ma et al 107 . and He et al 108 …”
Section: Pa Plus Deep Learningmentioning
confidence: 99%
“…8,9 Some researchers have proposed the restoration of resolution through deep neural networks, which would allow the focus to shift towards improving imaging speed during data collection. 10,11 However, training such models necessitates an extensive number of high-resolution images, which poses a challenge in the context of limited biomedical datasets for deep learning. The shortage of biomedical data raises the question of whether it is possible to train a neural network using a minimal number of high-resolution images or even just one.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high optical absorption contrast and good ultrasound resolution, photoacoustic imaging (PAI) has proven to be a promising tool for vascular imaging based on endogenous contrast with blood hemoglobin [13,14]. So far, PAI has been applied in studies of functional connectivity [15], neurovascular coupling [16], ischemic stroke [17] and obesity [18].…”
Section: Introductionmentioning
confidence: 99%